The Role of Regulatory T Cells in the Biology of Graft Versus Host Disease - Beres, Amy; Drobyski, William (Frontiers in Immunology, 2013)
Graft versus host disease (GVHD) is the major complication of allogeneic hematopoietic stem cell transplantation. GVHD is characterized by an imbalance between the effector and regulatory arms of the immune system which results in the over production of inflammatory cytokines. Moreover, there is a persistent reduction in the number of regulatory T (Treg) cells which limits the ability of the immune system to re-calibrate this proinflammatory environment. Treg cells are comprised of both natural and induced populations which have unique ontological and developmental characteristics that impact how they function within the context of immune regulation. In this review, we summarize preclinical data derived from experimental murine models that have examined the role of both natural and induced Treg cells in the biology of GVHD. We also review the clinical studies which have begun to employ Treg cells as a form of adoptive cellular therapy for the prevention of GVHD in human transplant recipients.